The finance of air transport services in Ireland - Brennan, Peter (Statistical and Social Inquiry Society of Ireland, 1951)
I begin with a few words by way of definition of the scope of this paper. The finance it is to be concerned with is that of commercial aviation as an Irish industry. Accordingly, no attempt is made to cover the finances of the various foreign airlines which participate in the country's external traffic, except in so far as they have incidentally been a source of local airport turnover. So also with regard to the small amount of private and non-commercial flying that is engaged in: some of the figures we will be reviewing, e.g., for receipts in respect of landing fees at the State airports, will have been influenced slightly by this traffic, but apart from such effects it is not taken into account. Lastly, it did not seem practicable to try to follow out employment and income effects of the aviation industry (including capital outlay on acquisition and construction) on other Irish industries, and the revenue picture will be to that extent incomplete.
Read before the Society, 3 November 1950
Keywords: Air transport in Ireland; Financing air transport services in Ireland; Irish aviation sector; Aer Lingus; 314.15